Divergence insufficiency associated with high myopia - Masato Wakakura (Dove Medical Press, 2010)
Hiromi Kohmoto, Kenji Inoue, Masato WakakuraInouye Eye Hospital, Chiyoda-ku, Tokyo, JapanPurpose: Divergence insufficiency is generally regarded as a neurological event. While high myopia is not a well-known cause of divergence insufficiency, we frequently encounter divergence insufficiency in high-myopia patients. Thus, the purpose of this study was to report detailed information on such cases and examine mechanisms that might potentially be responsible for this disorder.Methods: We investigated 20 cases of high myopia (>-6 D) with divergence insufficiency, 20 cases of high myopia without double vision, and 10 normal cases as controls. Using magnetic resonance imaging (MRI), a coronal image 6 mm anterior to the eyeball–optic nerve junction was measured and used to examine the extraocular muscle (EOM) path shift and angle of the eye. Higher angles in each patient were used for statistical comparison.Results: In high-myopia patients with divergence insufficiency, ocular axis measurements ranged from 24.8 to 31.0 (mean ± SD: 27.6 ± 1.6) mm. In high-myopia patients without double vision, the ocular axis length was 27.6 ± 1.3 mm. In normal cases, the ocular axis length was 23.5 ± 1.0 mm. The EOM angles in these patients ranged from 100 to 140 (112.9 ± 9.7) degrees, which was significantly higher (P < 0.05) than that seen in the high-myopia patients without double vision (average EOM angle, 99.2 ± 2.8 degrees) and normal cases (average EOM angle, 97.9 ± 3.8 degrees). However, orbital lengths in the patients were 41.0 to 48.9 (44.6 ± 2.3) mm, which also differed from the high-myopia patients without double vision (average orbital length, 49.9 ± 2.0 mm) significantly (P < 0.05). In normal cases, average orbital length was 45.5 ± 1.6 mm.Conclusion: In high-myopia patients with divergence insufficiency, nasal shift of the superior rectus and an inferior shift of the lateral rectus were observed, but the orbital lengths were normal. Divergence insufficiency may be caused mechanically by shifts of the EOM due to the presence of a long axis. Therefore, high myopia with a long axis can be considered to be a risk factor for the occurrence of divergence insufficiency.Keywords: divergence insufficiency, high myopia, MRI, extraocular muscle